Preparation, structure and optical properties of Nd2O3 doped Gd2O3-Ga2O3-GeO2 transparent glass-ceramics containing novel GdGaGe2O7 nanocrystal. Issue 13 (October 2022) - Lin, Xiangtao; Liang, Haozhang; Liu, Taoyong; Zhang, Ping; Jiang, Xingxing; Yu, Yanjun; Ning, Tianxiang; Lu, Anxian
Abstract: In this paper, Nd2 O3 doped Gd2 O3 -Ga2 O3 -GeO2 ternary glass was prepared by traditional melting method. DSC was used to characterize the thermodynamic properties of the parent glass and its crystallization mechanism was discussed. The structure of the glass ceramics containing novel GdGaGe2 O7 nanocrystal was measured by XRD, SEM and EDS, and the properties were characterized by transmittance and emission spectroscopy. The results show that the glass-ceramics has obvious advantages in fluorescence performance, which the emission intensity at 1060 nm is up to 5.5 times higher than that of the parent glass. Among them, the sample nucleated at 740 ℃ for 6 h and crystallized at 840 ℃ for 1 h has the best performance, which the emission intensity increased by 1.6 times when the transmittance decreased by only 1.6%. The material has great application potential in 1.06 µm band solid-state lasers.